Redesain Kemasan dan Pengaruhnya Terhadap Persepsi Merek Produk AMDK Lokal Air FREZZ - Sonhaji Arif; Amalia Hartiningrum (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2025)
Packaging functions not only as a product container but also as a strategic visual communication medium that shapes brand image and influences consumer purchasing decisions, particularly in the highly competitive bottled drinking water (AMDK) market. This study aims to examine the impact of packaging label redesign on enhancing visual attractiveness and brand differentiation of the local brand AIR FREZZ. The research employs a mixed-method approach using the Design Thinking framework, consisting of empathize, define, ideate, prototype, and test stages. User evaluation was conducted by comparing the old and redesigned packaging through a Likert-scale questionnaire administered to 40 respondents. The assessment focused on visual modernity, clarity of information, packaging attractiveness, brand perception, and purchase intention. The results indicate a significant improvement across all evaluation aspects, with an average increase of 1.40 points after the redesign. These findings demonstrate that simplified visual elements, consistent color schemes, and improved information hierarchy positively affect perceived quality and strengthen brand image. This study confirms that packaging plays a vital role as a branding.